Design Smart Helmet System with GSM for Safety Monitoring Systems (International Journal of Scientific Research in Science and Technology, 2025)
The increasing frequency of motorcycle accidents globally calls for innovative safety measures, with smart helmets emerging as a vital advancement. This paper presents the design and implementation of a smart helmet system integrating multiple sensors and communication technologies to monitor rider safety in real time. The system employs dual Arduino Uno microcontrollers—one embedded in the helmet and the other on the motorcycle—communicating via a 433 MHz RF link. An alcohol sensor embedded in the helmet restricts motorcycle operation under intoxicated conditions, while an MPU6050 accelerometer and gyroscope detect head movements and impacts. The vehicle unit includes a GSM module for sending emergency alerts and a relay-driven headlight control system. Experimental results confirm that this integrated system can effectively detect critical safety events and enhance emergency response capabilities. The proposed smart helmet design demonstrates high potential for reducing accident severity and enforcing responsible riding behaviour.
Keywords: Smart Helmet; Embedded Systems; Arduino; RF Communication; Alcohol Detection; MPU6050; GSM; Motorcycle Safety